BEYOND LEGISLATIONS: ETHICAL ISSUES IN DOMESTIC WORK IN NIGERIA - Ogbechie, Rose; Oyetunde, Kabiru (PEOPLE: International Journal of Social Sciences, 2019)
Recent studies show that domestic work, which cut across age and gender, can have adverse and exploitative consequences for workers, particularly in an unregulated environment. Due to these concerns, international organizations have enacted legislation for a regulated legal environment for domestic work for member nations to domesticate. Nigeria, as a member nation and signatory to the conventions and recommendations, has failed to enact legislation that will regulate the domestic work contractual terms. This article reviews the experiences of domestic workers in Nigeria concerning the abuses and exploitations they suffer in the hands of their employers. The ethical implications of the employers' attitude towards domestic workers are considered. Drawing on the qualitative methodological approach, primary data were collected from 26 interviews with domestic workers in Lagos, Nigeria. Also, secondary data from newspaper and magazine reports were analyzed. Germane ethical issues such as long hours of work, workload, lack of voice, abuses and ill-treatment, health and safety, maternity protection, are explored from the reported experiences of the workers and policy recommendations are made on the urgent need for the state to enact stringent legislation to stop unethical practices in the domestic work industry.